Is the transcranial magnetic stimulation an adjunctive treatment in fibromyalgia patients? - Yağcı, İlker; Ağırman, Mehmet; Öztürk, Demet; Eren, Beyhan (AVES, 2014)
Objective: To investigate the effectiveness of low-frequency (LF) repetitive transcranial magnetic stimulation (rTMS) to the motor cortex area in fibromyalgia patients who are resistant to medical treatment. Material and Methods: A total of 25 patients were randomly assigned to the study, who were in the active rTMS (n=13) or sham stimulation (n=12) group. For the rTMS group, the main stimulation parameters were 90% of motor threshold for 60 seconds at 1 Hz and a 45-second interval between each train. Ten sessions of low-frequency rTMS, which had a total of 1200 pulses at each session, were applied to the left primary motor cortex area daily over a period of 2 weeks. For the sham group, the same parabolic coil was placed at 90 degrees angles to the motor cortex area, and the patients received 10 sessions of sham stimulation. The outcome parameters were pain intensity, which was measured by visual analog scale (VAS), Fibromyalgia Impact Questionnaire (FIQ), and the Beck Depression Inventory (BDI). Results: A significant improvement in pain intensity, FIQ, and BDI scores was seen at the 10th day and first and third months in both groups. Although the mean of parameters of the rTMS groups was better than the sham group, the difference did not reach statistical significance, except FIQ scores at the 10th day in the real rTMS group. Conclusion: Patients with fibromyalgia who enroll in real TMS did not present significant differences in long-term follow-ups with respect to those who enrolled in the sham TMS group.

Amaç: Medikal tedaviye dirençli fibromiyalji hastalarında motor korteks alana uygulanan düşük frekanslı tekrarlayıcı transkraniyal manyetik stimülasyonun (tTMS) etkinliğini araştırmak. Gereç ve Yöntemler: Toplam 25 hasta randomize olarak aktif ve plasebo gruplarına ayrılarak çalışmaya alındı. Aktif tTMS grubu için stimülasyon sol primer motor korteks üzerinden motor eşik değerin %90’ı hesaplanarak 1 Hz ve 20 dakika uygulandı. Her seansta 1200 uyarı olmak üzere, iki hafta boyunca toplam 10 seans tedavi uygulandı. Plasebo grup için, parabolik koil 90° açı ile motor kortekse yerleştirildi ve aynı şekilde toplam 10 seans stimülasyon uygulandı. Sonuçlar, ağrı için vizüel analog skalası (VAS), Fibromiyalji Etkinlik Anketi (FIQ) ve Beck Depresyon Skalası (BDS) ile değerlendirildi. Bulgular: Her iki grupta da tedavi sonunda, 1 ve 3. ay sonunda ağrı derecesinde, FIQ ve BDS’de anlamlı iyileşme gözlendi. Ancak, aktif tTMS grubunda iyileşme plasebo gruba göre daha iyiydi. Tedavi sonu FIQ skorlarında aktif grupta, plasebo gruba göre istatistiksel olarak anlamlı iyileşme gözlendi. Diğer değerlendirmelerde gruplar arasında istatistiksel farklılık saptanmadı. Sonuç: Primer motor korteks üzerine düşük doz tTMS uygulamasının uzun süreli takiplerde fibromiyalji hastalarında plaseboya göre anlamlı iyileşme göstermediği görülmüştür
Transkraniyal magnetik stimulasyon fibromiyalji hastalarında ek bir tedavi yöntemi mi?
WOS: 000343521400006
Keywords: Fibromyalgia; Transcranial Magnetic Stimulation; Pain; Fibromiyalji; Transkraniyal Manyetik Stimülasyon; Ağrı